Health literacy in clinical‐high‐risk individuals for psychosis: A systematic mixed‐methods review. Issue 6 (27th January 2019) - Haidl, Theresa K.; Seves, Mauro; Eggers, Susanne; Rostamzadeh, Ayda; Genske, Anna; Jünger, Saskia; Woopen, Christiane; Jessen, Frank; Ruhrmann, Stephan; Vogeley, Kai
Abstract : Objective: Numerous studies suggest that health literacy (HL) plays a crucial role in maintaining and improving individual health. Empirical findings highlight the relation between levels of a person's HL and her/his clinical outcome. To date, the role of HL in persons at‐risk for psychosis has not been systematically reviewed. Methods: We conducted a systematic review using a mixed‐methods approach to analyse a variety of study types. Peer‐reviewed publications were systematically searched in PUBMED, Cochrane Library, PsycINFO and Web of Science. Results: The search string returned 10587 publications. After screening, 15 quantitative, four qualitative studies and two reviews were included. Only one study assessed HL as primary outcome, assessing knowledge and beliefs about psychosis among the general population. In the other studies, sub‐dimensions of HL were investigated. None of the publications operationalized HL or it's sub‐dimensions with a validated measure. Conclusions: A lack of understanding of their condition, and fear of stigmatization, were associated with a delay in help‐seeking among people with clinical‐high‐risk state for psychosis. Family members, school personnel, general practitioners and the internet play a crucial role in the HL process. Considerable barriers in obtaining adequate specialist support emphasize the urgent need of a "HL environment" for persons at risk for psychosis.